Effect of Myristica fragrans on PGC1α and Synaptophysin Expression in Male Wistar Rats Hippocampus - Veronica, Fifi; Goenawan, Hanna; Bahjah, Firda Hanan; Najmi, Nuroh; Lesmana, Ronny (Journal of Biomedicine and Translational Research, 2024)
Background: Nutmeg is an indigenous plant from Indonesia that has been used extensively in herbal treatment. Nutmeg seed extract (NuSE) contains the active compound macelignan, which exhibits pharmacological activities. A previous study stated that NuSE is PPARγ or peroxisome proliferator-activated receptor gamma agonist that potentially enhances synaptic signal modulation. PPARγ activation can activate PGC1α or peroxisome proliferator-activated receptor gamma coactivator-1 alpha as the primary regulator of mitochondrial biogenesis. Mitochondria are involved in synaptic transmission. Increased modulation of signals at synapses can increase neuroplasticity, potentially improving the brain's cognitive function, as seen by the amount of Synaptophysin in the synaptic vesicle membrane for evaluating synaptogenesis.Objective: This research demonstrates how nutmeg seed extract (NuSE) affects PGC1α and synaptophysin expression compared with DHA or docosahexanoieac acid, which has been evidenced to promote neurite growth.Methods: Twenty-four Wistar male rats aged eight weeks were divided into four groups (control, PGA group, NuSE group, and DHA group). The treatment group was administered for 12 weeks using a gavage. After that, the rats were sacrificed, and the hippocampus neurons were collected. The PGC1α and Synaptophysin mRNA expression was measured using semiquantitative reversed PCR, visualized with electrophoresis, and then quantified with ImageJ.Results: This study showed that NuSE increased synaptophysin and PGC1α mRNA expressions compared to the control group with significance statistic (p=0.017, p<0,05) in synaptophysin expression but did not increase PGC1α expression significantly (p=0.364, p>0,05).Conclusion: In conclusion, nutmeg seed extract (NuSE) impacts synaptogenesis in synaptophysin expression to modulate synaptic transmission.